The music is called to transform the ego mind (Confluenţe Bibliologice, 2026)
At the book launch of composer Gheorghe Mustea participants were invited to listen his music. All genres of music created by the composer have been presented: symphonic music, vocal-symphonic, opera, chamber (vocal and instrumental), choral, theatre and ﬁlm, light-music and popular style. The book containes an audio CD.
Keywords: book launch; Gheorghe Mustea (1951)